NUCLEAR ALIGNMENT - CLASSICAL DYNAMIC-MODEL FOR THE U-238 U-238 SYSTEM - Sharma, S. S.; Galetti, D. (American Physical Soc, 1992)
Dynamical properties of the U-238-U-238 system at the classical turning point, specifically the distance of closest approach, the relative orientations of the nuclei, and deformations have been studied at the sub-Coulomb energy of E(lab) = 6.07 MeV/nucleon using a classical dynamical model with a variable moment of inertia. Probability of favorable alignment for anomalous positron-electron pair emission through vacuum decay is calculated. The calculated small favorable alignment probability value of 0.116 is found to be enhanced by about 16% in comparison with the results of a similar study using a fixed moment of inertia as well as the results from a semiquantal calculation reported earlier.